Mallory-Weiss syndrome in four hemodialysis patients: a case study - Shuai-Shuai Shi; Xian-Zhu Yang; Xiao-ye Zhang; Lei Huang; Hui-Dan Guo; Shuang-fang Li; Wei Zhang; Yi-Qiang Zhang (BMC Nephrology, 2023)
Abstract Background Hemodialysis patients are prone to gastrointestinal bleeding, and Mallory-Weiss syndrome (MWS) is one of the causes. Mallory-Weiss syndrome is often induced by severe vomiting, manifests as upper gastrointestinal bleeding, and is self-limited with a good prognosis. However, mild vomiting in hemodialysis patients can lead to the occurrence of MWS, and the mild early symptoms are easy to misdiagnose, leading to the aggravation of the disease. Case presentation In this paper, we report four hemodialysis patients with MWS. All patients displayed symptoms of upper gastrointestinal bleeding. The diagnosis of MWS was confirmed by gastroscopy. One patient had a history of severe vomiting; however, the other three reported histories of mild vomiting. Three patients received the conservative hemostasis treatment, and the gastrointestinal bleeding stopped. One patient underwent the gastroscopic and interventional hemostasis treatments. The conditions of three of the patients improved. Unfortunately, one of the patients died due to the cardia insufficiency. Conclusions We think that the mild symptoms of MWS are easily covered up by other symptoms. This may lead to delays in diagnosis and treatment. For patients with severe symptoms, gastroscopic hemostasis is still the first choice, and interventional hemostasis can also be considered. For patients with mild symptoms, drug hemostasis is the first consideration.